Artificial Intelligence: The Future of Education - Bimalendu Pendy (CV. Publikasi Indonesia, 2021)
Artificial Intelligence (AI) has the potential to transform the way we teach and learn. In recent years, there has been a growing interest in the application of AI in education, with a range of initiatives and products emerging in the market. This review article provides an overview of the literature on the use of AI in education, focusing on the following areas: personalized learning, intelligent tutoring systems, natural language processing, gamification, and ethics.The article begins by discussing personalized learning with AI, highlighting the potential benefits of using AI to tailor learning experiences to individual students' needs and preferences. The article then explores intelligent tutoring systems, which use AI to provide students with personalized feedback and support. The use of natural language processing in education is also discussed, including the potential for AI to facilitate language learning and communication skills. The article then examines gamification and AI, discussing how gamification can be used to increase student engagement and motivation, and how AI can enhance the effectiveness of gamified learning environments. The ethical considerations of using AI in education are also discussed, including issues around privacy, bias, and transparency. the article concludes by summarizing the current trends and future directions in the use of AI in education. The potential of AI to revolutionize education is significant, but there are also challenges to be addressed. The review article highlights the need for further research to fully understand the potential of AI in education and to ensure that its use is ethical and effective. Overall, the review article suggests that AI has enormous potential to transform the future of education and highlights some of the key areas where AI is likely to have the most impact.